A case study on space downsizing from single detached house to a condominium unit - Arcangel, Carmela Patricia O.; Buencamino, Lorena M. (2007)
Different types of condominium units, low, middle or high rise are now available to Filipinos of different socio-economic status. The purpose of this study was to determine, evaluate, compare and try to understand their attitude towards the changes in the use of space in condominium units of Filipino families who used to live in single detached houses. It also aims to describe the coping mechanisms that they have employed with these changes. This study was conducted on four households that belong to the middle-middle class Filipino family composed of four members. They are living in a two bedroom condomium unit in Andalucia Building, Vista de Lago, Tuktukan, Taguig and were all residents of single detached houses. The study made use of qualitative method of research in analyzing data and gathered information using questionnaires, pictures, floor plans and a logbook. The results of this study indicated that condominium units can be multi-functional and socio-petal spaces as consequences to its space limitations. Furthermore, it shows that downsizing meant not only reduced space but reduced occupants and personal items as well. As a result, the respondents were able to cope by combining activities, use of Filipino adaptability and creativity. The preference for flexible spaces, concept of a dirty kitchen, values of pakitang-tao and pakikisama, were revealed in the coping mechanisms that the respondents employed.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Space (Architecture); Condominiums